2003
DOI: 10.1373/49.7.1149
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 3-Hydroxy Fatty Acids in Tissues after Intraperitoneal Injection of Endotoxin

Abstract: Background: 3-Hydroxy fatty acids (3-OH FAs) with 10-to 18-carbon chain lengths are constituents of the endotoxin [lipopolysaccharide (LPS)] of gram-negative bacteria. We investigated whether these FAs may be used as chemical markers in measuring endotoxin concentrations in mammalian tissue samples. Methods: We used gas-liquid chromatography-tandem mass spectrometry to measure 3-OH FAs in serum and tissues (heart, liver, and skeletal muscles) of rats after intraperitoneal injection of Escherichia coli LPS. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 12 publications
(9 reference statements)
2
31
1
Order By: Relevance
“…In earlier studies, the direct quantitative assay of 3HM was conducted by using GC/MS ( 8,10,11,21,22 ). In the present study, a highly signifi cant correlation was observed between GC/MS and HPLC/MS/MS methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies, the direct quantitative assay of 3HM was conducted by using GC/MS ( 8,10,11,21,22 ). In the present study, a highly signifi cant correlation was observed between GC/MS and HPLC/MS/MS methods.…”
Section: Discussionmentioning
confidence: 99%
“…They may thus produce false positive or false negative results ( 9 ). Quantitation of 3HM by GC/MS or GC/MS/MS corresponds to the direct measurement of LPS mass ( 8,10,11 ), but the detection of small amounts of 3HM in complex media is restricted by the limited amounts of lipid-rich samples that can be loaded on GC columns.…”
Section: Hplc/ms/msmentioning
confidence: 99%
“…Earlier studies [15,16] have shown that the distribution of 3-OH FAs in mammalian tissues and in blood can be detected by GLC-MS ion trap instrumentation. An experimental model of germ-free rats indicated a dual origin of these compounds in the blood and soft tissues: because of the unique structure of LPS it is believed that 3-OH FAs are chemical markers of Gram--negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…We previously used 3-hydroxy fatty acids (3-OH FAs) for monitoring endotoxin levels in the blood and sera of rats [15]. 3-OH FAs, structural constituents of the lipid A part of LPS, are chemical markers of endotoxin and are quantified by an analytic method [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharides were prepared with phenol-water extraction method (Westphal and Jann, 1965) and purified on Sepharose 2B column in 0.01 M NH 4 HCO 3 (Romanowska, 1967) as detailed previously (Rybka et al, 2003). Samples of rat serum from previous investigation (Szponar et al, 2003) were used. Samples of the phage T4 preparations cultured on wild type strain E. coli B were obtained from Bacteriophage Laboratory in our Institute.…”
Section: Methodsmentioning
confidence: 99%